China Male EFL Teachers’ Professional Identity in Hebei Province Higher Institutions - Shanfeng, Liu; Raja Harun, Raja Nor Safinas (Jurnal Pendidikan Bitara UPSI, 2024)
There are three objectives of this study. Firstly, to explore the process and types of the development of the professional identity among China male EFL teachers in higher institutions. Secondly, to investigate the factors that affect the development of China male EFL teachers’ professional identity. Thirdly, to constructs a theoretical model of construction of professional identity among China male EFL teachers in higher institutions. This study employs a qualitative research approach, through a case studies involving three male EFL teachers from Hebei province, aiming to enhance English learning outcomes and education quality in higher education, providing insights for university management policies in the field of foreign language education in China. This study has the following main findings: First, there are common and different features in the process of their professional identity development. The professional identity development of them is categorized into three types: the Multiple Identity Conflict type, the Identity Crisis type and the Identity Reconstruction type. Second, the factors affecting the identity development of EFL teachers in Chinese higher institutions are categorized into two groups which are personal factors and sociocultural factors. Third, by analyzing the actual, desirable and ideal identities of China male EFL teachers, this study constructs a professional identity and development model for Male EFL teachers in China higher institutions. The implications of this study for educational reform in higher institutions in China include two aspects: 1) The institutions should create a reasonable institutional environment for the professional development of Male EFL teachers, and 2) the institutions should give EFL teachers more humanistic care. As to EFL teachers, it is important to pay attention to the national policy at the macro level, and design one’s career rationally. It is also important to develop a sense of researcher identity and fully recognize that researcher identity is an important part of the professional identity of male EFL teachers and that the development of other identities play a key role in promoting teachers’ professional development.